2021
DOI: 10.7759/cureus.15704
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Small Bowel Extramedullary Plasmacytomas Presenting With Intestinal Obstruction

Abstract: Extramedullary plasmacytoma (EMP) is a plasma cell disorder involving soft tissues in the absence of clonal bone marrow involvement or destructive bone lesions. When present in the gastrointestinal (GI) tract, and specifically the small intestine, it can cause a wide range of symptoms including GI bleeding, obstruction, and abdominal pain. The diagnosis is challenging, as it can hold an indolent course, and is infrequently encountered in clinical practice. Diagnosis requires biopsy of the involved organ, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[ 2 , 11 ] Their clinical presentations varied, since symptoms are related to the effect of the mass on the surrounding structures. [ 2 , 12 ] Possible symptoms are abdominal pain, intestinal obstruction, intussusception, nausea, vomiting, constipation, weight loss, malabsorption, GI bleeding, and obstructive jaundice. [ 2 ] Our female patient also had EMP of the ileum, which is a primary type, although she had a past history of lymphoma 22 years ago.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 , 11 ] Their clinical presentations varied, since symptoms are related to the effect of the mass on the surrounding structures. [ 2 , 12 ] Possible symptoms are abdominal pain, intestinal obstruction, intussusception, nausea, vomiting, constipation, weight loss, malabsorption, GI bleeding, and obstructive jaundice. [ 2 ] Our female patient also had EMP of the ileum, which is a primary type, although she had a past history of lymphoma 22 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our case, Alnimer et al reported a case of multiple EMPs of the ileum in a 51-year-old woman who presented with small bowel obstruction and had a previous history of solitary plasmacytoma of the left acetabulum. [ 12 ] They described that their case developed multiple EMPs of the ileum 3 years after the diagnosis of SPB. [ 12 ] By contrast, our male patient developed metastasis in the left posterior epidural space of T 8–10 spine due to late diagnosis of EMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They most commonly arise from the head, neck, and upper respiratory tract. Solitary gastrointestinal (GI) plasmacytomas are even more unique, accounting for approximately 4% of extramedullary plasmacytomas [ 3 ]. Presenting symptoms depend on the location of the mass with abdominal pain, fatigue, GI bleeds, and altered bowel habits being the most reported for GI plasmacytomas in the literature [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of gastrointestinal EMPs vary with the location and progression of the tumor and lack specificity. Common clinical manifestations include abdominal pain, abdominal discomfort, changes in bowel habits, gastrointestinal bleeding and intestinal obstruction[ 8 - 12 ]. However, there are no reports of spontaneous perforation and abdominal abscess caused by EMP of the small intestine.…”
Section: Introductionmentioning
confidence: 99%